"Contextually" speaking: A survey of pragmatic learning abroad, in class, and online. (February 2015) - Taguchi, Naoko
Abstract: In order to acquire pragmatic competence, learners must have access to the target language input and opportunities for pragmatic practice. Over the last three decades, research has emerged to specify this fundamental condition of pragmatic learning. Existing studies fall primarily into three main categories: study abroad literature that focuses on students' learning pragmatics in the target language community, formal classroom environment where pragmatics is not the target of instruction, and digitally-mediated contexts in which communication takes place in virtual environments. This paper synthesizes key findings in these three contexts, and compares and contrasts the opportunities and challenges involved in each context, with the overall aim of revealing how each context supports pragmatic learning and development.